2019
DOI: 10.1371/journal.pone.0221824
|View full text |Cite
|
Sign up to set email alerts
|

The extraordinary osteology and functional morphology of the limbs in Palorchestidae, a family of strange extinct marsupial giants

Abstract: The Palorchestidae are a family of marsupial megafauna occurring across the eastern Australian continent from the late Oligocene through to their extinction in the Late Pleistocene. The group is known for their odd ‘tapir-like’ crania and distinctive clawed forelimbs, but their appendicular anatomy has never been formally described. We provide the first descriptions of the appendicular skeleton and body mass estimates for three palorchestid species, presenting newly-identified, and in some cases associated, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 51 publications
(54 reference statements)
5
26
0
Order By: Relevance
“…In this study, we set out to quantitatively test previous functional interpretations of the bizarre forelimb anatomy of Palorchestes, using 3D ROM mapping of elbow mobility with a comparative dataset of extant and extinct mammals. This multiaxial approach has confirmed that even when degrees of freedom available are maximised, Palorchestes has remarkably low elbow mobility compared to other mammals, although this joint may not have been quite as 'fixed' as previously thought (Flannery & Archer, 1985;Richards et al, 2019). Our results highlight that even 'hinge' joints such as the elbow, which have traditionally been assumed to be uniaxial in their movements, can in fact show complex multiaxial rotations in maximal osteological ROM.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In this study, we set out to quantitatively test previous functional interpretations of the bizarre forelimb anatomy of Palorchestes, using 3D ROM mapping of elbow mobility with a comparative dataset of extant and extinct mammals. This multiaxial approach has confirmed that even when degrees of freedom available are maximised, Palorchestes has remarkably low elbow mobility compared to other mammals, although this joint may not have been quite as 'fixed' as previously thought (Flannery & Archer, 1985;Richards et al, 2019). Our results highlight that even 'hinge' joints such as the elbow, which have traditionally been assumed to be uniaxial in their movements, can in fact show complex multiaxial rotations in maximal osteological ROM.…”
Section: Discussionsupporting
confidence: 76%
“…We suggest this forelimb anatomy may have been used either in scratch digging or, perhaps more likely, bipedal browsing-a functional niche unrepresented among living mammals (Coombs, 1983). This may partly explain the lack of functional similarities recovered in our results, and makes sense given their koala-like claw morphology (Richards et al, 2019). This compromise in locomotor efficiency in favour of other forelimb uses was evidently successful for a time-Palorchestes azael is the most common and widely distributed palorchestid, recovered in Middle to Late Pleistocene deposits right across the eastern half of the Australian continent (Davis & Archer, 1997)-until their existence was cut short by the extinctions that decimated Australia's megafauna some 40,000 years ago (Hocknull et al, 2020).…”
Section: Palorchestes Posture Locomotion and Forelimb Usementioning
confidence: 78%
See 1 more Smart Citation
“…– or identify anatomical novelties – such as apomorphically robust/gracile limbs possibly associated with particular ecologies (e.g. Richards et al ., 2019). Emphatically, the results of mass estimation should never be presented as a point estimate.…”
Section: Resultsmentioning
confidence: 99%
“…Given data availability, we settled on a total of 21 species (13 extinct; 8 extant) from five different functional/taxonomic groups: ( i ) 5 vombatiform herbivores: Diprotodon optatum (2786 kg; extinct) ( Wroe et al, 2004 ), Palorchestes azael (1000 kg; extinct) ( Richards et al, 2019 ), Zygomaturus trilobus (500 kg; extinct) ( Johnson, 2006 ), Phascolonus gigas (200 kg; extinct) ( Johnson, 2006 ), and Vombatus ursinus (common wombat; 25 kg; extant) ( McIlroy, 1996 ; Saran et al, 2011 ); ( ii ) 7 macropodiform herbivores: Procoptodon goliah (250 kg; extinct) ( Johnson and Prideaux, 2004 ), Sthenurus stirlingi (150 kg; extinct) ( Johnson and Prideaux, 2004 ), Protemnodon anak (130 kg; extinct) ( Johnson, 2006 ), Simosthenurus occidentalis (120 kg; extinct) ( Johnson, 2006 ), Metasthenurus newtonae (55 kg; extinct) ( Johnson, 2006 ), Osphranter rufus (red kangaroo; 25 kg; extant) ( McIlroy, 2008 ), and Notamacropus rufogriseus (red-necked wallaby; 14 kg; extant) ( Strahan, 1991 ); ( iii ) 3 omnivorous (but primarily plant-eating) large birds: Genyornis newtoni (200 kg; extinct) ( Johnson, 2006 ), Dromaius novaehollandiae (emu; 55 kg; extant) ( Sales, 2007 ), and Alectura lathami (brush turkey; 2.2 kg; extant) ( Jones et al, 1995 ); ( iv ) 4 carnivores: Thylacoleo carnifex (marsupial ‘lion’; 110 kg; extinct) ( Johnson, 2006 ), Thylacinus cynocephalus (marsupial ‘tiger’; 20 kg; extinct) ( Jones and Stoddart, 1998 ), Sarcophilus harrisii (devil; 6.1 kg; extinct in mainland Australia, but extant in Tasmania — see below) ( Guiler, 1978 ), and Dasyurus maculatus (spotted-tail quoll; 2.0 kg; extant) ( Belcher et al, 2008 ); and ( v ) 2 monotreme invertivores: Megalibgwilia ramsayi (11 kg; extinct) ( Johnson, 2006 ), and Tachyglossus aculeatus (short-beaked echidna; 4.0 kg; extant) ( Nicol and Andersen, 2007 ).…”
Section: Choice Of Species and Body Mass Distributionmentioning
confidence: 99%